Can political violence ever be justified? - Frazer, Elizabeth; Hutchings, Kimberly, 1960- (Cambridge, UK ; Medford, MA : Polity, 2019)
"In this book, Elizabeth Frazer and Kimberly Hutchings ask whether the use of violence can ever be justified in politics. Using examples from contemporary politics and political thought, they carefully explore the various justificatory strategies that have been deployed, and conclude that all attempts to justify political violence invariably fail"--
Introduction: the question of political violence -- Violence and justification -- Simple justifications of simple violence -- Complicating matters -- The meaning of political violence -- Against the justification of political violence -- Conclusion: political violence can never be justified -- Sources and further reading.
Includes bibliographical references and index.
Keywords: Political violence